Analysis and simulations of multifrequency induction hardening. (April 2015) - Hömberg, Dietmar; Petzold, Thomas; Rocca, Elisabetta
Abstract: We study a model for induction hardening of steel. The related differential system consists of a time domain vector potential formulation of Maxwell's equations coupled with an internal energy balance and an ODE for the volume fraction of austenite, the high temperature phase in steel. We first solve the initial boundary value problem associated by means of a Schauder fixed point argument coupled with suitable a priori estimates and regularity results. Moreover, we prove a stability estimate entailing, in particular, uniqueness of solutions for our Cauchy problem. We conclude with some finite element simulations for the coupled system.